Distribution of xenobiotic metabolising enzyme genotypes in different Tunisian populations - Slah Ouerhani; Islem Ben Bahria; Kamel Rouissi; Lotfi Cherni (Taylor & Francis Group, 2017)
Background: The N-acetyltransferase 2 (NAT2) and glutathione transferase enzymes play a crucial role in the metabolism of xenobiotics. Genetic polymorphisms affecting these enzymes can modify their activities with an effect on individual susceptibility for different pathologies. These metabolic phenotypes occur with varying prevalence in different populations. Aim: This study sought to analyse the prevalence of important allelic variants of NAT2, GSTM1 and GSTT1 in different Tunisian populations and compare them to other previously reported data. Subjects and methods: A total of 253 unrelated subjects from different Tunisian populations participated in this study. Subjects were examined with respect to the frequency of slow NAT2, GSTM1*0 and GSTT1*0 genotypes. Results: The frequency of 'slow' NAT2, GSTM1*0 and GSTT1*0 genotypes in the Tunisian population were, respectively, estimated at 23.3%, 53.75% and 29.24%. The frequency of slow NAT2 and GSTM1*0 genotypes were significantly different between the North, Centre and South of Tunisia. However, this study doesn't report any significant differences in the genotype distribution between Cosmopolitan, Arab and Berber populations. Conclusions: In conclusion, these data indicate that the Tunisian population is highly heterogenic and, therefore, a strict definition of the populations involved in studies investigating the clinical effect of polymorphisms is required.